Sensitivity analysis of nems cantilever to detect volatile organic compounds using finite element method - JAYAPRAKASH CH; N Siddaiah (Kuwait Journal of Science)
Nano Electro Mechanical System (NEMS) based cantilever is the alternate form of Micro Electro Mechanical system (MEMS) with dimensional changes in perspectives like Thickness, length, and width. The advantage of the dimensional change leads to great improvement in sensitivity and performance with portable structure. In this paper, a stepped nanocantilever sensor is designed for the detection of volatile organic compounds. The same is compared with the conventional micro cantilever in order to assess the sensitivity. The advantage of incorporating longitudinal cut at fixed end of the cantilever is investigated for different materials with load analysis and stress distributed results. COMSOL Simulation software is used to perform the analysis of nanocantilever and the result shows sensitivity increased with longitudinal cut and type of material which exhibits good sensitivity. In this research, we suggest a stepped cantilever structure that uses FEM to calculate the change in deflection owing to various loads in both static and dynamic analyses. Similarly, changes in resonance frequency for changes in beam thickness are examined using parametric study. The experimental results from COMSOL simulation are found that the displacement occurred in proposed cantilever that the deflection sensitivity 2.85 x10-9m under maximum stress of 3.32 x10-9 N/m2. From the dynamic analysis, resonant frequency occurs at 20nm thickness is 2.8x10 7 Hz, and at 30nm is 3.5 x 107 Hz respectively.